Conditional knockout of heparin‐binding epidermal growth factor‐like growth factor in the liver accelerates carbon tetrachloride‐induced liver injury in mice. Issue 4 (9th August 2012) - Takemura, Takayo; Yoshida, Yuichi; Kiso, Shinichi; Saji, Yukiko; Ezaki, Hisao; Hamano, Mina; Kizu, Takashi; Egawa, Mayumi; Chatani, Norihiro; Furuta, Kunimaro; Kamada, Yoshihiro; Iwamoto, Ryo; et al.
<x xml:space="preserve">Abstract</x> Aim: We previously demonstrated that heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF) is induced in response to several liver injuries. Because the HB‐EGF knockout (KO) mice die in utero or immediately after birth due to cardiac defects, the loss of function study in vivo is limited. Here, we generated liver‐specific HB‐EGF conditional knockout mice using the interferon‐inducible Mx‐1 promoter driven cre recombinase transgene and investigated its role during acute liver injury. Methods: We induced acute liver injury by a single i.p. injection of carbon tetrachloride (CCl4) in HB‐EGF KO mice and wild‐type mice and liver damage was assessed by biochemical and immunohistochemical analysis. We also used AML12 mouse hepatocyte cell lines to examine the molecular mechanism of HB‐EGF‐dependent anti‐apoptosis and wound‐healing process of the liver in vitro. Results: HB‐EGF KO mice exhibited a significant increase of alanine aminotransferase level and also showed a significant increase in the number of apoptotic hepatocytes assessed by terminal deoxynucleotidyl transferase dUTP nick end labeling staining at 24 h after CCl4 injection. We also demonstrated that HB‐EGF treatment inhibited tumor necrosis factor‐α‐induced apoptosis of AML12 mouse hepatocytes and promoted the wound‐healing response of these cells. Conclusion: This study showed that HB‐EGF plays a protective role during acute liver injury.